Effect of spectral degradation on speech intelligibility and cortical representation - Choi, Hyo Jung; Kyong, Jeong-Sug; Won, Jong Ho; Shim, Hyun Joon (Frontiers in Neuroscience, 2024)
makes a significant contribution by demonstrating the impact of spectral channel bands on speech intelligibility and cortical responses, representing higher-level cognition of speech using a semantic oddball paradigm. Through experiments involving 20 participants, we observed a clear effect of channel bands on speech intelligibility and N2 and P3b cortical responses. These findings suggest that the N2 and P3b responses reflect the channel effect in the cortex, indicating less efficient semantic integration due to reduced spectral information in speech. Such results enhance our understanding of how spectral information influences cortical speech processing, with implications for developing advanced algorithms in hearing aids for individuals with hearing impairments or degraded auditory input. Furthermore, a better understanding of the impact of sparse spectral information on speech intelligibility and neural representation could provide valuable insights for designing public spaces such as auditoriums or transportation hubs.